2006
DOI: 10.1167/iovs.05-1627
|View full text |Cite
|
Sign up to set email alerts
|

The Prostanoid EP2Receptor Agonist Butaprost Increases Uveoscleral Outflow in the Cynomolgus Monkey

Abstract: The prostanoid EP2 receptor agonist butaprost appears to lower IOP by increasing uveoscleral outflow, according to both physiological and morphologic findings. Although the prostanoid EP2 receptor is structurally and functionally distinct from the FP receptor, the effects of EP2 and FP receptor stimulation on aqueous humor outflow are similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 29 publications
1
72
0
Order By: Relevance
“…It seems that the long-term 24-hour travoprost efficacy is only slightly greater than that reported over the short-term (with up to 3 mo follow-up). Possible reasons for this small difference include the mechanism of action of travoprost, which involves remodeling of the extracellular matrix, [30][31][32] hence it is logical to assume a small increase in efficacy after the first few months of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that the long-term 24-hour travoprost efficacy is only slightly greater than that reported over the short-term (with up to 3 mo follow-up). Possible reasons for this small difference include the mechanism of action of travoprost, which involves remodeling of the extracellular matrix, [30][31][32] hence it is logical to assume a small increase in efficacy after the first few months of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the fact that PGE 2 , a nonspecific EP receptor agonist, has been shown to have a strong potential for IOP reduction (Gabelt et al 2004), it is highly likely that this autacoid participates in the ocular hypotensive effect of epinephrine. It is suggested that the discussed effect can be achieved through the PGE 2 -induced increase of the uveoscleral outflow, but at present there is no definite evidence that PGE 2 increases this type of outflow, even though there are some data (Nilsson et al 2006) pointing to this possibility.…”
Section: Mechanism Of Actionmentioning
confidence: 97%
“…Relaxation of TM cells as a result of a reduction of actin stress fibers and vinculin localization at focal adhesions was observed using such analogs [171]. Interest is increasing in the development of EP 2 and EP 4 receptor agonists for the treatment of POAG, with one such EP 2 agonist having been shown to reduce IOP by increasing both unconventional and conventional flow, facilitated by the relaxation of SC and by decrease in contractility and collagen deposition at the TM [172][173][174]. These effects are similar to those of traditional FP receptor agonists, however these, in contrast, may increase TM contractility.…”
Section: New Classes Of Drugmentioning
confidence: 99%